1990
DOI: 10.1128/iai.58.9.3009-3014.1990
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic inactivation of cytokines by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa alkaline protease and elastase are thought to contribute to bacterial invasiveness, tissue damage, and immune suppression in animals and patients infected with the bacterium. This study examined the ability of the two proteases to inactivate a number of cytokines that mediate immune and inflammatory responses. Human recombinant gamma interferon (rIFN-y) and human recombinant tumor necrosis factor alpha were inactivated by both proteases. Murine rIFN-,y was relatively resistant to alkalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…Structural components of the microorganism, such as Lipoarabinomannan of Mycobacteriae sp., can directly inhibit the responsiveness of macrophages to IFN-y (98). Substances produced by replication of bacteria, such as proteases produced by Pseudomonas aeruginosa, can destroy the activity of the IFN--y molecule through specific enzymatic degradation (86). In addition, infection with a pathogen such as Mycobacterium aviurn can increase the production of other cytokines (such as TGF-P) which in turn interfere with the antimicrobial activities of IFN-y (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural components of the microorganism, such as Lipoarabinomannan of Mycobacteriae sp., can directly inhibit the responsiveness of macrophages to IFN-y (98). Substances produced by replication of bacteria, such as proteases produced by Pseudomonas aeruginosa, can destroy the activity of the IFN--y molecule through specific enzymatic degradation (86). In addition, infection with a pathogen such as Mycobacterium aviurn can increase the production of other cytokines (such as TGF-P) which in turn interfere with the antimicrobial activities of IFN-y (7).…”
Section: Resultsmentioning
confidence: 99%
“…However, no beneficial effect of IFN-y treatment was observed in burned mice infected with Pseudomonas aeruginosa, a common burn pathogen (43). Later studies by Parmely and associates have indicated that proteases, such as alkaline protease and elastase, produced during Pseudomonas infections specifically cleave IFN-y resulting in inactive forms of the cytokine (86). When a strain of Pseudomonas deficient in its ability to produce alkaline protease was used in the burn/infection model, IFN-y successfully protected mice from infection (90).…”
Section: Surgical Wound Models Of Infectionmentioning
confidence: 99%
“…P. aeruginosa proteases hinder a range of cytokine activities and are also able to induce degradation of cytokines (59). Examples include AprA degradation and inactivation of human interferon γ (INF-γ) (90), and inactivation of human tumour necrosis factor-α (TNF-α) by LasB (90,91). Both INF-γ and TNF-α play an important role in the host immune response, with a lack of INF-γ resulting in auto-inflammatory diseases (92,93) and TNF-α involved in systemic inflammation and apoptosis (77).…”
Section: Cytokine Degradationmentioning
confidence: 99%
“…In addition to the direct action of microbial proteases, it is now evident that the activation of endogenous host protease zymogens such as clotting cascade and the inactivation of most of the plasma protease inhibitors contribute to damaging host tissues. Bacterial proteases may also potentate inflammatory processes, activate the bradykinin generating system, degrade immunoglobulins, and complement factors amongst other effects [22][23][24][25]. The precise role of the protease produced by A. pleuropneumoniae and its participation in porcine pleuropneumonia pathogenesis remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%